Multiple Myeloma of the Orbit - Mona Hassan; Zaid Alirhayim; Laila Sroujieh; Syed Hassan (Case Reports in Ophthalmological Medicine)
The authors report a case of a 62-year-old female with history of multiple myeloma who presents with complains of swelling and pain in her right eye. On examination, it was found that she has proptosis, chemosis, and diplopia along with decreased vision. Initial workup and treatment did not yield significant results, eventually she was found to have myelomatous changes in her right orbit on MRI and was diagnosed with multiple myeloma of the orbit which resolved solely with radiation. This case tends to highlight the importance of considering myeloma of the orbit as a very important and early differential diagnosis in a patient with a history of multiple myeloma presenting with a swollen and painful eye.